Часовий хід останнього скорочення в тетанусі m. gastrocnemius (cap. med) в алкоголізованих щурів за умов критичної васкулярної ішемії задніх кінцівок. Зміна вектора розвитку м’язової сили - Мельничук, Олексій; Melnychuk, Olexiy (Східноєвропейський національний університет імені Лесі Українки, 2014)
Проаналізовано зміну часового ходу і векторних характеристик останнього м’язового скорочення в послі¬довних тетанічних пробігах m. gastrocnemius (cap. med.) в алкоголізованих щурів. Виявлено достовірні зміни вектора розвитку м’язової сили. Змін часового ходу скорочення в експериментальних групах щурів, порівняно з контролем, не виявлено. The Change of Muscle Tension Vector Growth. In this article was studied contractile characteristics and muscle tension vector growth changes of the last contraction of m. gastrocnemius (cap. med) tetanic runs sequence in alcohol-intoxicated rats. m. gastrocnemius (cap. med) mechanical activity was conducted in isometric mode under direct electrical stimulation. Muscle contraction contractile intervals analysis suggests to the conclusion about the absence of significant changes in the time course of m. gastrocnemius (cap. med) muscle contraction in alcohol-intoxicated rats compared with non-alcoholic. However, in alcohol-intoxicated and non-alcoholic rats muscle develops tension at an acute angle, compared to the control, where tg φ angle numerical values are approximate to the straingth angle values decreasing in the second half of the experiment. The change of muscle tension vector growth in both experimental rat groups are indicates the intense ischemic-associated muscle tissue ultrastructural changes and muscle fatigue development accelerate.
Time Course of the Last Contraction of m. gastrocnemius (cap. med) Tetanus in Alcohol-intoxicated Rats under Critical Vascular Hind Limbs Ischemia
Keywords: m. gastrocnemius; алкогольна інтоксикація; васкулярна ішемія; вектор розвитку м’язової сили; контрактильні характеристики; m. gastrocnemius; alcohol intoxication; vascular ischemia; muscle tension vector growth; contractile properties